Cyber Law & Human Behavior: Global Insights - Firmansyah, Febrian Dwi; Purwaningsih, Sri Budi; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This dataset, "Cyber Law and Behavioral Reactions," sourced from lens.org, compiles 3,194 journal articles focusing on the intersection of Cyber Law and human behavior. Through meticulous curation and analysis, this dataset highlights global research trends, emphasizing Psychology as a central field of study and the prevalence of open-access scholarly works. Dominated by institutions like Erasmus University Rotterdam and authors like Didier Bigo, the dataset's focus on the United States offers diverse perspectives. The dataset's goal was to explore the nuances of Cyber Law's impact on human behavior. Methodologically, rigorous step-by-step data collection and analysis were employed. Results underscore Psychology's prominence and the prevalence of open-access works. The dataset's implications make it an invaluable resource for researchers delving into Cyber Law's intricate relationship with human behavior. Highlights : Comprehensive dataset on Cyber Law and human behavior trends Emphasizes Psychology's centrality and prevalence of open-access works Valuable resource for understanding Cyber Law's impact on human behavior Keywords: Cyber Law, Human Behavior, Dataset, Psychology, Open Access